HEPATOPROTECTIVE ACTIVITY OF POLYHERBAL EXTRACT AGAINST CCL4 INDUCED LIVER DAMAGE IN RATS - Sangeeta Singh, Kamran Javed Naquvi, Amarjeet Singh & Abdul Wadood Siddiqui (South Eastern European Journal of Public Health, 2025)
The current work evaluated the hepatoprotective effect of ethanolic extracts of Eichhornia crassipes, Ipomoea aquatica, and Hydrilla verticillate using silymarin against the CCl4-induced in-vivo rat model at varying doses. Histological investigations were used to confirm the hepatoprotective action of EC, IP & HV, which was assessed by assessing serum biomarker levels. Rat’s livers were effectively shielded from the damage caused by CCl4 by the plant extract. Serum levels of bilirubin, total protein, alkaline phosphatase, serum glutamic-pyruvic transaminase and serum glutamic oxaloacetic transaminase were significantly decreased. In contrast to silymarin, the histological analysis showed a notable repair of liver structure. The traditional usage of polyherbs to comprehend its hepatoprotective potential has been scientifically validated by this investigation.